2013
DOI: 10.1002/anie.201308376
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 6‐Alkylated Phenanthridine Derivatives Using Photoredox Neutral Somophilic Isocyanide Insertion

Abstract: Bring to light: The first visible‐light‐promoted somophilic isocyanide insertion occurs using an iridium photocatalyst. This efficient synthetic approach provides a rapid entry to 6‐alkylated phenanthridine derivatives (see scheme). The reactions proceed at room temperature in good to excellent yields with broad substrate scope and under environmentally friendly conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
88
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 283 publications
(89 citation statements)
references
References 94 publications
0
88
0
1
Order By: Relevance
“…Ir(ppy) 2 (dtbbpy)PF 6 (E 1/2 IV/*III = À0.96 V vs. SCE), which has been proved to be an efficient reductant to produce phenyl radicals from 2a under visible light irradiation, 11 was firstly tested as a photocatalyst. When a solution of 1a and 2a in CH 3 CN was irradiated with 3 W white LED in the presence of Ir(ppy) 2 (dtbbpy)PF 6 and Na 2 CO 3 for 24 h, the desired isoquinoline 3a was obtained in 47% isolated yield, structure of which was established ambiguously by the single crystal X-ray diffraction analysis 15 (Table 1, entry 1). With the screening of solvents, we found that DMF, DMSO and CH 2 Cl 2 were inferior to CH 3 CN with less than 40% yield (entries 2-4).…”
mentioning
confidence: 99%
“…Ir(ppy) 2 (dtbbpy)PF 6 (E 1/2 IV/*III = À0.96 V vs. SCE), which has been proved to be an efficient reductant to produce phenyl radicals from 2a under visible light irradiation, 11 was firstly tested as a photocatalyst. When a solution of 1a and 2a in CH 3 CN was irradiated with 3 W white LED in the presence of Ir(ppy) 2 (dtbbpy)PF 6 and Na 2 CO 3 for 24 h, the desired isoquinoline 3a was obtained in 47% isolated yield, structure of which was established ambiguously by the single crystal X-ray diffraction analysis 15 (Table 1, entry 1). With the screening of solvents, we found that DMF, DMSO and CH 2 Cl 2 were inferior to CH 3 CN with less than 40% yield (entries 2-4).…”
mentioning
confidence: 99%
“…On the basis of the experimental observation and literatures [44][45][46][47][48][49][50][51][52][53] …”
Section: Resultsmentioning
confidence: 99%
“…For instance, Carreira reported a cobaltcatalyzed photochemical synthesis of allylic trifluoromethanes from styrene derivatives using 2,2,2-trifluoroethyl iodide [38]. On the basis of this work and in connection with our interest radical cyclizations [39][40][41][42][43], we communicate herein our recent studies on the visible-light-promoted trifluoroethylation of 2-isocyanobiaryl using the cheap and available reagent CF 3 CH 2 I as the source of the CH 2 CF 3 group to afford 6-trifluoroethyl-phenanthridine derivatives (Scheme 1) [44][45][46][47][48][49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 96%
“…[1] Taking advantage of the reductionp otentials of a-halo carbonyl compounds,g eneration of alkyl radicals through singleelectront ransfer and theira ddition to alkenes, [2] alkynes, [3] isocyanides, [4] anda romatic rings [5] have been reported. However, the use of vinylazidesast he radical acceptors in visible-light reactions remains ac hallenge,m ainly because of theird enitrogenatived ecomposition to highly strained azirines via vinyl nitrene intermediates.…”
Section: Visible Lightmentioning
confidence: 99%